Theoretical Interpretation of Polarized Light-Induced Supramolecular Orientation on the Basis of Normal Mode Analysis of Azobenzene as Hybrid Materials in PMMA with Chiral Schiff Base Ni(II), Cu(II), and Zn(II) Complexes - Ito, Maiko; Akitsu, Takashiro; Palafox, Mauricio A. (Journal of Applied Solution Chemistry and Modeling, 2016)
We have prepared hybrid materials of azobenzene and chiral Schiff base Ni(II), Cu(II), and Zn(II) complexes and investigated their linearly or circularly polarized UV (ultraviolet) light-induced supramolecular orientation with polarized electronic and IR spectra or CD (circular dichroism) spectra. The experimental FT-IR (Fourier transfer-infrared) spectra of azobenzene molecules were recorded at room temperature, and the results were compared with quantum chemical theoretical values using B3LYP, M052X, and M062X DFT (density functional theory) methods. The interaction of azobenzene with PMMA was simulated. Molecular geometry, vibrational wavenumbers, and thermodynamic parameters were calculated in all these systems. With the help of specific scaling procedures for the computed wavenumbers, the experimentally observed FT-IR bands were analyzed and assigned to different normal modes of the molecule. Most modes had wavenumbers in the expected range, and the error obtained was in general very low. Several general conclusions were deduced.